The libro de caja y manual de cuentas de mercaderes (1590), by Bartolomé Salvador de Solórzano, and the origins of the accounting nomenclature in spanish - Quirós García, Mariano (2019)
In 1590, through the Madrid press of Pedro de Madrigal, the Libro de caja y manual de cuentas de mercaderes, by Bartolomé Salvador de Solórzano, was published. It is the first accounting treaty written in Spanish, which addresses, for the first time in our language, the double entry system. This paper describes its relationship with the history of Spanish and European accounting. Likewise, the accounting terminology that configures it is analyzed, calling attention to the author’s linguistic concerns. Finally, its status is studied in the fields of Spanish language history and lexicography. This has allowed us to identify not only first documentations, but also loans and certain «phantom» words and meanings that force us to rethink the etymology of some words.